DISTANT SHOCKWAVE LITHOTRIPSY IN CHILDREN - S.N. Zorkin; A.V. Akopyan; M.I. Bakanov; E.N. Tsygina; L.E. Skutina; L.E. Vorob'eva (Union of pediatricians of Russia, 2009)
Shockwave lithotripsy implemented in the clinical practices in the 1980-s drastically altered the treatment approach for the urolithiasis and took a leading place in the therapy of this disease. The key task of the distant shockwave lithotripsy is to provide for the fast, reliable, safe and noninvasive kidney and renal duct litholysis. The article highlights the outcome of the shockwave lithotripsy application on Econolith 3000 for the treatment of 27 children. The results of the performed treatment indicated the high efficiency and low invasiveness of this method to eliminate the concrements, as well as the perspective of its use, including in the infants. Shockwave lithotripsy allows the specialists to abandon the traumatic surgeries.Key words: distant shockwave lithotripsy, urolithiasis, children.